Foundations for model-based systems engineering : from patterns to models - Holt, Jon; Perry, Simon; Brownsword, Mike (Professional applications of computing series ;, 2016)
The practice of Model-based Systems Engineering is becoming more widely adopted in industry, academia and commerce and, as the use of modelling matures in the real world, so the need for more guidance on how to model effectively and efficiently becomes more prominent. This book describes a number of systems-level 'patterns' (pre-defined, reusable sets of views) that may be applied using the systems modelling language SysML for the development of any number of different applications and as the foundations for a system model. Topics covered include: what is a pattern? Interface definition pattern; traceability pattern; test pattern; epoch pattern; life cycle pattern; evidence pattern; description pattern; context pattern; analysis pattern; model maturity pattern; requirements modelling; expanded requirements modelling; process modelling; competence modelling; life cycle modelling; defining patterns; and using patterns for model assessment, model definition and for model retro-fitting. This book forms a companion volume to both 'SysML for Systems Engineering - a model-based approach' and 'Model-based Requirements Engineering', both published by the IET. Whereas the previous volumes presented the case for modelling and provided an in-depth overview of SysML, this book focusses on a set of 'patterns' as the basis of an MBSE model and their use in today's systems engineering community.